A Comparative Analysis of Participating and Non-Participating Households in Pro-Poor Tourism in Southern Shaanxi, China. Issue 3 (4th May 2019) - Lo, Kevin; Li, Jie; Wang, Mark; Li, Cong; Li, Shuzhuo; Li, Ying
ABSTRACT: The ability of the poor to participate gainfully in pro-poor tourism (PPT) projects is an important but understudied factor in determining poverty alleviation impact. This study aims to address this knowledge gap by exploring the relationship between participation, income, and livelihood capital at the household level using China as a case study. We examined eight PPT projects in southern Shaanxi, a poverty-stricken region that has abundant tourism resources. Our comparative approach revealed the differences between participating and non-participating households. We found that the level of participation is 36% and the main form of participation was through family-run businesses. Participating households earned a significantly higher income than non-participating households. The former also had significantly more material, financial, political, social, and human capital. These findings underscore the capability of tourism as a poverty alleviation tool and reveal problems regarding the growing inequality between participating and non-participating households.